ANALISIS SISTEM INFORMASI PENGELOLAAN DATA TRANSAKSI PEMBELIAN CONSUMER UNTUK MANAJEMEN PEMBELIAN PERUSAHAAN - WUISAN, DEWI S S (ISTEK WIDURI, 2020)
This study aims to determine and also analyze the information system on purchases, especially purchases of goods made by the customer at PT.ABC will help in the management of corporate purchases. The research method used in this study is qualitative research, which is needed to get a picture of the relationship between the subject and the object under study. Where the subject is PT. ABC, as for the object is the information system of purchasing goods by customers. Data collection used in this study through the process of interviews, observation and literature study. To overcome the problems in this research, an information system design for managing consumer purchase transaction data was made to be built using the PHP programming language and Microsoft Access database. Analysis of the data used is to use user analysis and analysis of the current system. The results achieved in this study are able to simplify and speed up data access by updating the financial section, the purchasing department, and the purchasing manager in this case greatly helps the company in monitoring goods.